\(y=x^2+x\)上の点 (2, 6) における接線の方程式を求めてみる。
1 | 1 | 0 | |
---|---|---|---|
-4 | -4 | ||
4 | 4 | ||
1 | 5 | -4 |
よって,\(y=5x-4\)
\(f(x)=x^2-2x+2\), \(y=f(x)\)上の点\((a,f(a))\)における接線の方程式を求めてみる。
1 | -2 | 2 | |
---|---|---|---|
\(-a^2\) | \(-a^2\) | ||
\(2a\) | \(2a\) | ||
\(1\) | \(2a-2\) | \(-a^2+2\) |
よって,\(y=(2a-2)x-a^2+2\)
\(f(x)=x^3-3x^2+2\), \(y=f(x)\)上の点\((a,f(a))\)における接線の方程式を求めてみる。
1 | -3 | 0 | 2 | |
---|---|---|---|---|
\(-a^2\) | \(-a^2\) | \(-2a^3+3a^2\) | ||
\(2a\) | \(2a\) | \(4a^2-6a\) | ||
\(1\) | \(2a-3\) | \(3a^2-6a\) | \(-2a^3+3a^2+2\) |
よって,\(y=(3a^2-6a)x-2a^3+3a^2+2\)
強力 😃